Analysing the spatial patterns and trends of urban growth in Rohtak city, India. Issue 1 (31st December 2022) - Sharma, Manju; Kumar, Sandeep
ABSTRACT: The phenomenon of urban growth is a complicated one. It is the outcome of numerous social, economic, ecological, cultural, and even political circumstances. Rapid urbanization generally occurs due to the disbursement of peripheral prime agricultural land, destroying the natural landscape in the process. Rohtak city is a fast-growing city in India's National Capital Region (NCR). The physical development of the city and land use/land covers are measured using Landsat satellite data. ArcGIS and Erdas software have been used for making the map, image processing and classification. In this study, five major land use and cover categories, built-up area, agricultural land, vegetation, bare/open land and water bodies, are used. The spatial arrangement and urban growth trends in Rohtak are examined using Shannon's Entropy index. Results show that Rohtak city has witnessed four-fold growth in its built-up area (from 1640.79 hectares in 1991 to 6686.36 hectares in 2021) in thirty years of the study. However, the planned and unplanned residential and commercial arrangements have appeared on all sides throughout the periods. Yet, the city expanded its limits mainly in north, north-eastern and south-eastern sides along with the major transport routes to New Delhi, Sonipat and Panipat. It is primarily a result of government policies and proximity to the capital city.